Karl Rahner's Theological Aesthetics - Fritz, Peter Joseph (Book collections on Project MUSE., 2014)
"This innovative book discloses Karl Rahner's foremost achievement: discovering and delineating an ethos of Catholicism, a multifaceted and comprehensive approach to the life in Christ. Karl Rahner's Theological Aesthetics does so by placing the German Jesuit and his teacher, philosopher Martin Heidegger, into a richly detailed dialogue on aesthetics. This book treats classic Rahner topics such as anthropology and Christology. But it breaks new ground by exploring themes such as angels, Mary, and the apocalypse, justaposed with analogous philosophical topics in Heidegger."--Jacket